1997
DOI: 10.1002/(sici)1098-2736(199708)34:6<633::aid-tea6>3.3.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Beginning science teacher cognition and its origins in the preservice secondary science teacher program

Abstract: The objectives of this study were to (a) identify the major tenets of a preservice secondary science education program as expressed by science education faculty, (b) identify knowledge structures that beginning secondary science teachers have constructed about the teaching and learning of science, and (c) identify the correlatives that exist between the first two objectives. The study was grounded in the postulates of teacher cognition in that teachers construct their own schema from their experiences in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
5

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 0 publications
3
40
0
5
Order By: Relevance
“…Following Shulman's (1986) ideas about PCK, other researchers developed their own categories of teacher knowledge (e.g. Borko and Putnam, 1996;Grossman, 1990;Adams and Krockover, 1997). Particularly, Adams and Krockover (1997) develop a framework for investigating teacher knowledge by synthesizing Elbaz's (1983) unique category of teacher knowledge, "knowledge of self" and Grossman's (1990) definition of teacher knowledge.…”
Section: Pedagogical Content Knowledge (Pck)supporting
confidence: 91%
“…Following Shulman's (1986) ideas about PCK, other researchers developed their own categories of teacher knowledge (e.g. Borko and Putnam, 1996;Grossman, 1990;Adams and Krockover, 1997). Particularly, Adams and Krockover (1997) develop a framework for investigating teacher knowledge by synthesizing Elbaz's (1983) unique category of teacher knowledge, "knowledge of self" and Grossman's (1990) definition of teacher knowledge.…”
Section: Pedagogical Content Knowledge (Pck)supporting
confidence: 91%
“…The systematic induction program needs developing with the aim of teacher professionalism and initializing more productive teacher career. In addition, more contextual factors must be considered to encourage beginning teachers to be concentrating on students' engagement in meaningful science activities with the scaffolding by mentor teachers at school (Adams and Krockover, 1997;Choi et al, 2009). It has been reported that beginning teachers make effort to conduct the research into their practices of teaching science as inquiry in learning communities where they could interact with mentor teachers or educators (Bianchini and Cavazos, 2007;Roehrig and Luft, 2006;Kwak, 2009).…”
Section: Discussion and Implicationmentioning
confidence: 99%
“…New teachers, although intent on teaching science for all, also find it difficult to start instruction from the knowledge, interests, and experiences of their students; many underscore the importance of student-centered classrooms, but continue to implement teacher-centered curriculum and instruction (Simmons et al, 1999). Forces outside beginning teachers-students, curriculum materials, course requirements, and school structures-further constrain their efforts to describe the nature of science in contemporary ways or to engage students in rich and varied investigations (Adams & Krockover, 1997;Brickhouse & Bodner, 1992;Munby, Cunningham, & Locke, 2000;Trumbull, 1999). Additional research is needed to more fully understand "how teachers learn to teach demanding content to all students, a question that is central to the current reform agenda" (Feiman-Nemser & Remillard, 1996, p. 85).…”
Section: Introductionmentioning
confidence: 99%